Recent synthesis of aminophosphonic acids as potential biological importance - Naydenova, Emilia D; Todorov, Petar T; Troev, Kolio D (Amino acids, 2010)
Aminophosphonic acids are an important group of medicinal compounds, and their synthesis has been a focus of considerable attention in synthetic organic chemistry as well as medicinal chemistry. Although the phosphonic and carboxylic acid groups differ considerably with respect to shape, size, and acidity, α-aminophosphonic acids are considered to be structural analogues of the corresponding amino acids and the transition state mimics peptide hydrolysis. This review summarizes recent developments in the synthesis, characterization and biological activity of α-aminophosphonic acid and N-analogues. An account of both uses will be presented, emphasizing one of the potential future developments, and some implications in medicinal chemistry are also disclosed. In addition, a brief account on the characterization of N-(phosphonomethyl) glycine derivatives will be presented.